Characterization of polymer coating on palm kernel shell-reinforced polypropylene composites - Nordin, Mohd Nur Azmi; Nik Ruzi, Nik Mohd Ammar Zharfan; Ramli, Mizah; Syahrial, Fadhli; Zakaria, Mohamad Shukri; Zainal Abidin, Muhammad Zaimi; Abd Razak, Jeefferie (Trans Tech Publications Ltd, 2022)
Natural fibers are increasingly used in the polymer industry as bio-composites for a wide range of applications, such as the interior part of the automobile, interior material boards, decking panels, and many others. The presence of cellulose, which is hydrophilic in nature, lessens the mechanical properties of the bio-composites by increasing water uptake into the composites or also may affect the interfacial bonding between the polymer matrix and the fibers because the matrix is hydrophobic. The former may occur due to the surface of the bio-composites being highly exposed to water sources, e.g., high humidity in the air, rainwater, and many more. Thus, an additional layer on the surface of the bio-composites needs to be applied to protect the surface from water sources. The coating may be used for decorative, protective, or both purposes. This study aims to investigate the performance of polymer coating on a bio-composite substrate. The coating solution, chitosan-pectin-calcium chloride (CPC) solution was prepared, and the compatibility and wettability of the coating solution with the polymer-based bio-composites substrate were evaluated. The substrate was dipped into the coating solution for two minutes and hung to allow the excess coating solution to drop while drying the substrate. The performance of coating on the bio-composite substrate is evaluated by measuring the contact angle θ and average maximum bond strength σb of the sample with the different numbers of coating layers. It is found that the wettability of the contact angle indicates a lower contact angle for two-layer compared to one layer of the CPC coating due to the hydrophilicity of the coating materials.